Programming instruction using a micro robot as a teaching tool. Issue 1 (3rd September 2013) - Yamanishi, Teruya; Sugihara, Kazutomi; Ohkuma, Kazumasa; Uosaki, Katsuji
ABSTRACT This practical report analyzes a programming class using a micro robot (MR), the smallest soccer robot in the RoboCup world competition. This class examined the effect of using the MR as the actual equipment employed in programming. Questionnaire results on this class revealed that these teaching materials evoked a heightened programming interest among students. Moreover, the problems related to programming instruction using an MR were better understood; therefore, a strategy for improving the related problems is discussed here. © 2013 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:109–116, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21582